Simultaneous Determination of Gallic Acid, Ellagic Acid, and Eugenol in Syzygium aromaticum and Verification of Chemical Antagonistic Effect by the Combination with Curcuma aromatica Using Regression Analysis - Jung-Hoon Kim; Chang-Seob Seo; Seong-Sil Kim; Hyekyung Ha (Journal of Analytical Methods in Chemistry)
This study was designed to perform simultaneous determination of three reference compounds in Syzygium aromaticum (SA), gallic acid, ellagic acid, and eugenol, and to investigate the chemical antagonistic effect when combining Curcuma aromatica (CA) with SA, based on chromatographic analysis. The values of LODs and LOQs were 0.01–0.11 μg/mL and 0.03–0.36 μg/mL, respectively. The intraday and interday precisions were <3.0 of RSD values, and the recovery was in the range of 92.19–103.24%, with RSD values <3.0%. Repeatability and stability were 0.38–0.73% and 0.49–2.24%, respectively. Compared with the content of reference and relative peaks in SA and SA combined with CA (SAC), the amounts of gallic acid and eugenol were increased, while that of ellagic acid was decreased in SAC (compared with SA), and most of peak areas in SA were reduced in SAC. Regression analysis of the relative peak areas between SA and SAC showed r2 values >0.87, indicating a linear relationship between SA and SAC. These results demonstrate that the components contained in CA could affect the extraction of components of SA mainly in a decreasing manner. The antagonistic effect of CA on SA was verified by chemical analysis.